PROBLEMATIKA DAKWAH DI DUNIA ISLAM DAN SOLUSI FILOSOFISNYA - Rahmat Ramdhani (JURNAL ILMIAH SYI'AR, 2013)
Identify the problems of propaganda (Ghodayah Da’wah) in the Islamic world can be divided into two aspects, namely the internal and external aspects. Namaun, both internally and externally indicate that the condition of Muslims is still underdeveloped in terms of human resources, both economic, educational and sociopolitical, so that linearly affects the development of Islamic preaching itself. Surely it is not just on the Inventory, but also must be able to provide a choice of solutions to solve, so the condition of Muslims in the international world could be better.